2016
DOI: 10.1021/acschemneuro.6b00018
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fused Arylpyrimidinone Based Allosteric Modulators of the M1 Muscarinic Acetylcholine Receptor

Abstract: . (2016) Novel fused arylpyrimidinone based allosteric modulators of the M1 muscarinic acetylcholine receptor. ACS Chemical Neuroscience, 7 (5). pp. 647-661. ISSN 1948-7193 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/31897/1/acschemneuro%252E6b00018.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(129 reference statements)
2
14
1
Order By: Relevance
“…Consistent with the results of previous studies [21] , [22] , [26] , PF-06767832, VU6004256 and MIPS1780 have higher affinities at the M 1 mAChR compared to BQCA ( Table 1 ). However, the affinity of BQCA in our study is higher than previously reported values [18] , [27] , [31] , [37] for this compound. This could be due to different experimental conditions including radiolabelled antagonist used, membrane vs. whole cell binding-based assays, incubation time and temperature.…”
Section: Resultscontrasting
confidence: 93%
“…Consistent with the results of previous studies [21] , [22] , [26] , PF-06767832, VU6004256 and MIPS1780 have higher affinities at the M 1 mAChR compared to BQCA ( Table 1 ). However, the affinity of BQCA in our study is higher than previously reported values [18] , [27] , [31] , [37] for this compound. This could be due to different experimental conditions including radiolabelled antagonist used, membrane vs. whole cell binding-based assays, incubation time and temperature.…”
Section: Resultscontrasting
confidence: 93%
“…Excitingly, the amino acid residues of this extracellular allosteric site of the mAChRs show greater diversity between the different subtypes, thus providing the framework for designing mAChR subtype selective allosteric ligands. In fact, the allosteric sites of the M 1 and M 4 mAChRs have successfully been targeted by rationally designed synthetic allosteric ligands, with (now) a large number of subtype selective allosteric ligands available as pharmacological tools (Ma et al, 2009;Kuduk et al, 2010;Kuduk et al, 2011;Salovich et al, 2012;Le et al, 2013;Mistry et al, 2013;Croy et al, 2014;Huynh et al, 2015;Davoren et al, 2016a;Mistry et al, 2016a;Wood et al, 2016a;Davoren et al, 2016b;Mistry et al, 2016b;Wood et al, 2016b;Wood et al, 2017a;Wood et al, 2017b;Davoren et al, 2017;Long et al, 2017;Tarr et al, 2017;Bertron et al, 2018;Beshore et al, 2018;Dallagnol et al, 2018;Engers et al, 2019a;Engers et al, 2019b;Chopko et al, 2019;Jorg et al, 2019;Poslusney et al, 2019;Schubert et al, 2019;Temple et al, 2019;Temple et al, 2020a;Temple et al, 2020b). Since the orthosteric and allosteric sites are topographically distinct, two ligands can bind one receptor simultaneously.…”
Section: Targeting Specific Machr Subtypes Multiple Binding Sites At Machrsmentioning
confidence: 99%
“…Of note, in situations where the orthosteric ligand is a full agonist in both the absence and presence of modulator, the operational model can be simplified to allow for derivation of an overall combined modulatory effect, quantified through the composite parameter, αβ (Aurelio et al, 2009). Application of these allosteric models has been successful in determining structure activity relationships for allosteric modulators of multiple GPCRs including the adenosine A 1 (Ferguson et al, 2008;Aurelio et al, 2009;Aurelio et al, 2010;Aurelio et al, 2011;Valant et al, 2012a) the mAChRs (Mistry et al, 2013;Mistry et al, 2016b;Dallagnol et al, 2018;Jorg et al, 2019;Jorg et al, 2020), the mGlu receptors (Mueller et al, 2012;Gregory et al, 2013;Turlington et al, 2013) and the GLP1-R (Wootten et al, 2012;Wootten et al, 2013b;Hager et al, 2017).…”
Section: Quantifying Allosteric Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring opening of aryl B, replacing the tricyclic benzo[ h ]-quinazolin-4(3 H )-one core with quinazolin-4(3 H )-one, gives compound 25 . 104 Compound 25 shows improved “druglike-ness” with lower lipophilicity, topological polar surface area (tPSA), molecular weight and also reduces the toxic DNA-chelation concern for polyaromatic heterocycle scaffolds. The methyl group in the 8-position is critical to maintain affinity for the M 1 mAChR allosteric site compared to 22 with p K B and α β values of 5.15 and 380 for 25 and 5.88 and 370 for 22 , respectively, but lower intrinsic activity (τ B = 1.1) in radioligand binding experiments using FlpIN CHO cells.…”
Section: Recent Advances In the Discovery And Design Of Class A Gpcr mentioning
confidence: 99%